Experimental studies and mathematical simulation of intermittent infrared and convective drying of sweet potato (Ipomoea batatas L.) - Chikwendu, Daniel I. Onwude; Hashim, Norhashila; Abdan, Khalina; Janius, Rimfiel; Chen, Guangnan (Elsevier, 2019)
Intermittent infrared and convective drying (IIRCD) is a novel drying method that can enhance energy efficiency and quality of dried product. The mechanism of drying using this method is not yet fully understood. Mathematical models that describe the drying process of IIRCD for agricultural crops do not exist. In this study, a physics based mathematical model was developed to understand the mechanism of drying sweet potato using IIRCD. The model was based on shrinkage dependent diffusivity and evaporation phenomenon. COMSOL Multiphysics finite element software was employed for the model simulation. The simulation results of moisture and temperature distribution were validated by experimental drying data. The results fitted closely with experimental data. Drying of sweet potato using IIRCD was found to be more efficient in terms of final product quality compared to convective hot-air drying method.